Export upgrading and growth: the prerequisite of domestic embeddedness - Sandra Poncet; Felipe Starosta de Waldemar (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
Our work contributes to the literature relating output structure and economic development by showing that growth gains from upgrading are not unconditional. Relying on data from a panel of Chinese cities, we show that the level of capabilities available to domestic firms operating in ordinary trade is an important driver of economic growth. However, no direct gains emanate from the complexity of goods produced by either processing-trade activities or foreign firms. This suggests that the sources of product upgrading matter, and that domestic embeddedness is key in order for capacity building and technology adoption to be growth enhancing.
Keywords: F1; O11; O14; O40; O53; R1; 330; Economic complexity; export upgrading; FDI; processing trade; growth; China